INDONESIAN LEGAL SYSTEM STRUGGLE: A Lawful Plan in Order to Create Happiness for the People - Purwanto (Novateur Publications, 2022)
A. Historical Aspects and Socio-Cultural Basis: A Portrait of Legal Politics Article 1 (3) of the 1945 Constitution of the Republic of Indonesia affirms: "The State of Indonesia is a state of law", Recognition as a state of law implies that in the life of society, nation and state, law is something that is "supreme", and is used as a reference value in an effort to realize national goals as stated in the Preamble to the 1945 Constitution of the Republic of Indonesia.